Tanthawi Jauhari’s Interpretation of Celestial Movements and Its Fiqh Implications for Hijri Month Determination - Imam Labib Hibaurrohman; Farah Nuril Izza; Al Furqon Dono Hariyanto (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This article explores the concept of the movements of the Earth, Moon, and Sun as described in the exegesis Al-Jawahir Fi Tafsir Alquran Al-Karim, and its implications for determining the beginning of the Hijri months. The study aims to describe the views of Tanthawi Jauhari, a scholar and exegete, on understanding Qur’anic texts related to the celestial movements of the Earth, Moon, and Sun. Additionally, the paper discusses the contemporary relevance of his views in resolving debates between rukyah (moon-sighting) and hisab (astronomical calculations) within Islamic jurisprudence. Data collection was conducted through a documentation method, gathering both primary and secondary data. The primary data source was Tanthawi Jauhari’s interpretation in Al-Jawahir Fi Tafsir Alquran Al-Karim, while secondary data were drawn from relevant literature to support the analysis. The collected data were analyzed using content analysis methods. This study concludes that Tanthawi Jauhari’s concept of the Earth, Moon, and Sun emphasizes the Moon’s revolution around the Earth, while the Earth revolves around the Sun. He explains that the Earth’s rotation causes the alternation between day and night. However, his interpretation focuses solely on the synodic cycle of the Moon, without addressing the sidereal cycle. The variations in these celestial movements impact the visibility of the crescent moon (hilal), which may result in discrepancies in determining the beginning of the Hijri months. The article also highlights how Tanthawi Jauhari’s scientific approach could contribute to modern astronomical discussions regarding Islamic calendar calculations.